Navigating the Digital Age: The Role of Islamic Religious Education and Spiritual Intelligence in Shaping Elementary Students' Digital Well-Being - Saifullah (MADINA : Journal of Islamic Studies, 2026)
The rapid expansion of digital technology has transformed children's learning experiences and daily lives, raising concerns about their digital well-being. While previous studies have predominantly examined digital well-being from psychological and technological perspectives, limited attention has been given to the contribution of religious education and spiritual development in fostering healthy digital engagement among elementary school students. This study investigates the role of Islamic Religious Education (IRE) and Spiritual Intelligence (SI) in shaping students' Digital Well-Being (DWB) within the context of elementary education. Employing a sequential explanatory mixed-methods design, the study was conducted between February and April 2026 at two public elementary schools in Banda Aceh, Indonesia. The quantitative phase involved 200 students from Grades IV–VI selected through proportionate stratified random sampling, while the qualitative phase included interviews with two principals, four Islamic Religious Education teachers, and eight students selected through purposive sampling. Quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), whereas qualitative data were examined through thematic analysis. The findings indicate that Islamic Religious Education positively influences students' Spiritual Intelligence and Digital Well-Being. Spiritual Intelligence was also found to have a significant positive effect on Digital Well-Being and partially mediated the relationship between Islamic Religious Education and Digital Well-Being. Qualitative findings further revealed that the internalization of Islamic values, reflective religious practices, and moral guidance provided through Islamic Religious Education contribute to students' self-regulation, responsible technology use, and emotional balance in digital environments. This study proposes an integrated educational-spiritual framework that highlights the importance of Islamic Religious Education in promoting healthy digital behavior among elementary school students. The findings provide both theoretical and practical implications for strengthening character-based digital education in the contemporary digital era.